Relational Autonomy in Bioethics (Revista Iberoamericana de Bioética, 2023)
Bioethics was born in Georgetown with the intention of reinforcing patient autonomy in the face of interventionist medicine applied with traditional paternalistic criteria. Informed consent is elaborated as the putting into practice of “dry” autonomy which, in the depersonalization suffered by medicalized and commercialized medicine, has been ineffective. In recent decades, with a strong feminist influence, relational autonomy has developed, emphasizing that the exercise of autonomous decisions depends on social contexts, cultural criteria and biographical identity, in addition to being severely limited by negative socioeconomic conditions.Proclaiming autonomy as a principle has had little impact on social practices, including medicine. Here, the proposal is to promote relational autonomy through the use of relational ethics: ethics of recognition (Hegel/Honneth), ethics of resonance (Rosa) and ethics of responsiveness (Waldenfels). In addition, individual freedom and ethical relationality depend on cultivating self-care (Foucault).
Keywords: autonomy; ethics of recognition; ethics of resonance; ethics of care